Wellness Tourism Research - Rančić Demir, Milica (Academica turistica, 2022)
The paper presents the results of a bibliometric analysis of academic research covering the field of wellness tourism. The purpose of the article is to identify the structure of relationships between topics that were current in the past and topics that are current now. The aim of the research was to better understand the development of the field of wellness tourism, important constructs, authors, and resources with the help of bibliometric methods. For detailed research of the field of literature on wellness tourism, some two set bibliometric strategies were used: co-citation and keyword co-occurrence. In our bibliometric mapping of the wellness tourism research field, we have investigated the scientific production of articles over the years, the most important journals in the field, and keyword co-occurrence patterns. The obtained results of the study showed a significant increase in the number of publications related to wellness tourism. When it comes to the importance of individual journals, we have identified the 20 best journals that have published the most articles in this field. In wellness tourism research, we identified four clusters: health tourism research, tourism research, wellness topics, and wellness tourism research.
Keywords: bibliometrics; bibliometrija; keyword co-occurrence; literature review; pregled literature; sopojavnost ključnih besed; turizem; velnes; wellness tourism